Maternal investment in semi-domesticated reindeer (Rangifer t. tarandus L.) - Kojola, Ilpo (1989)
This paper investigates maternal investment in male and female offspring within a herd of semi-domesticated reindeer (Rangifer tarandus tarandus L.) in Kaamanen, Finnish Lapland (69° N, 27° E). Among calves born to cows weighing less than the mean of the herd (71 kg), the proportion of males increased as maternal body weight increased. The very smallest cows (weighing less than 60 kg) gave birth to a significant excess of females. Both the medium-sized and the largest cows produced a slight, nonsignificant excess of males. The body weight of cows was closely correlated with social rank. One year delay in the age of the first reproduction brought about a tendency to compensate for the lower number of offspring with high quality males. Overall, or in any category of maternal age or weight, the sex ratio of surviving offspring did not deviate from 1:1 or from the sex ratio born. Maternal investment for male vs. female offspring was temporally different. During gestation and the first life weeks of calf, cows invested most heavily in males. During later stages of lactation, cows rearing a male calf were able to compensate for a part of the heavier weight loss they suffered during calving. Preweaning investment in males was heavier in terms of the maternal weight change from one conception to the next. Mother's reproductive success in the subsequent year did not, however, depend on the sex of the reared calf. During the first post-weaning winter, female calves shared a feeding site (snow crater) with their mother twice as often as male calves did. Female calves gained, in terms of the decreased weight loss, advantage from maternal social rank. However, the weight loss of mother did not depend upon the sex of the calf. Females through the age of four years showed a tendency to associate with their mother. The results revealed in this study do not unambigiously support the hypothesis which predicts that superior females produce more male than female offspring. My results are consistent with assumption that selection will primarly eliminate the most unfit reproductive strategies. Male reproductive success is not necessarily most enhanced by an exceptionally heavy maternal investment.